Արմէն Օհանեան – Արշակ Չօպանեան առնչութիւնները - Մատթէոսեան, Վարդան; Բախչինեան, Արծուի (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Танцовщица, писательница, актриса и переводчица Армен Оганян (София Пирбудагян, 1887, Шамаха–1976, Мехико) жила в Париже с 1912 по 1931 год и поддерживала длительные профессиональные отношения с Аршаком Чобаняном. Dancer, writer, actress and translator Armen Ohanian (Sofia Pirbudaghian, 1888, Shamakha –1976, Mexico City) lived in Paris from 1912–1931 and maintained a long-term professional relationship with Archag Tchobanian.
Keywords: Արվեստագիտություն